King David and the frog - Ritzarev, Marina (Muzikološki zbornik, 2014)
The interrelations between the liturgical and paraliturgical genres of sacred music in both live practice and in historiography are explored. Parallels are found between eighteenth-century Russian and modern Hebrew religious music. The author's theory of the vernacular in music is applied to explain the stylistic openness in paraliturgical music (as a parallel to onto-vernacular folklore).
Keywords: duhovna glasba; folk music; govorjeni jezik; liturgično; ljudska glasba; paraliturgično